1992
DOI: 10.3759/tropics.1.243
|View full text |Cite
|
Sign up to set email alerts
|

An Estimation of Above Ground Tree Biomass of a Mangrove Forest in East Sumatra, Indonesia.

Abstract: Above ground tree biomass was estimated in Bruguiera parviflora, B. sexangula, and Rhizophora apiculata communities of a mangrove forest in Talidendang Besar, East Sumatra, Indonesia. The research was carried out from December 1990 to January 1991, and allometric relation method was used to estimate the above ground biomass of tree species having a diameter of 10 cm and over. The above ground biomass in this forest ranged from 42.94 to 89.68 t d.wt/ha in a B. parviflora community; 75.99 to 279.03 t d.wt/ha in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
13

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 10 publications
2
25
0
13
Order By: Relevance
“…Dari habitatnya, ekosistem mangrove memiliki tipe habitat berlumpur sampai lumpur dalam (Istomo, 1992dan Aksornkoae, 1993, Hamilton et al, 1984., Krasuss dan Allen. 2003), dipengaruhi oleh pasang dan penggenangan air laut (Hutchings dan Saenger, 1987, Kusmana, 1996, serta Snedeker dan Snedeker, 1984, serta dapat hidup pada kisaran salinitas rendah sampai tinggi (Hutchings dan Saenger, 1987, serta Aksorkonkoae, 1993. Selain kekhasan tersebut, ekosistem mangrove memiliki vegetasi yang memiliki berbagai macam manfaat dan fungsi seperti untuk mengurangi resiko abrasi (Hilmi et al, 2014a), penstabil zona pantai (Mazda et al, 1995), kemampuan untuk meredam gelombang pasang (Mazda et al, 1995dan Massel et al, 1999, resiko tsunami (Hilmi et al, 2014b., Kerr et al, 2006, serta Kathiresan dan Rajendran, 2005, habitat berbagai mikroorganisme (Elison, 2008dan Alfaro, 2006 dan bakteri pengurai, habitat berkembang biak berbagai fauna dan tempat migrasi satwa (Murdiyanto, 2003), mengurangi dan mengakumulasi berbagai bahan pencemar logam berat dann minyak (Wickramasinghe et al, 2009.…”
Section: Pendahuluanunclassified
“…Dari habitatnya, ekosistem mangrove memiliki tipe habitat berlumpur sampai lumpur dalam (Istomo, 1992dan Aksornkoae, 1993, Hamilton et al, 1984., Krasuss dan Allen. 2003), dipengaruhi oleh pasang dan penggenangan air laut (Hutchings dan Saenger, 1987, Kusmana, 1996, serta Snedeker dan Snedeker, 1984, serta dapat hidup pada kisaran salinitas rendah sampai tinggi (Hutchings dan Saenger, 1987, serta Aksorkonkoae, 1993. Selain kekhasan tersebut, ekosistem mangrove memiliki vegetasi yang memiliki berbagai macam manfaat dan fungsi seperti untuk mengurangi resiko abrasi (Hilmi et al, 2014a), penstabil zona pantai (Mazda et al, 1995), kemampuan untuk meredam gelombang pasang (Mazda et al, 1995dan Massel et al, 1999, resiko tsunami (Hilmi et al, 2014b., Kerr et al, 2006, serta Kathiresan dan Rajendran, 2005, habitat berbagai mikroorganisme (Elison, 2008dan Alfaro, 2006 dan bakteri pengurai, habitat berkembang biak berbagai fauna dan tempat migrasi satwa (Murdiyanto, 2003), mengurangi dan mengakumulasi berbagai bahan pencemar logam berat dann minyak (Wickramasinghe et al, 2009.…”
Section: Pendahuluanunclassified
“…The estimation of aboveground biomass of mangrove is not only provides increasingly valuable means for making comparisons among ecosystems but could also use to evaluate the productivity pattern, nutrient cycle and energy flow (Kusmana et al, 1992). Furthermore, in order to understand the forest ecosystem characteristics, the measurement of tree biomass is important.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that the mean above-ground biomass of 154.8 Mg•ha −1 was within the documented range of 40.70-279.03 Mg•ha −1 in the mangrove forests of East Sumatra, Indonesia (Kusmana et al 1992), or of 123.5-383.5 Mg•ha −1 in the mangrove forests of Dominican Republic (Sherman et al 2003). The present value of AGB was almost identical to that (159 Mg•ha −1 ) of Rhizophora apiculata Bl.…”
Section: Aboveground and Belowground Biomassmentioning
confidence: 89%